Difficult Decisions in Colorectal Surgery - Hyman, Neil.; Umanskiy, Konstantin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book looks at the highest quality evidence available to guide management decisions in colorectal surgery. The chapters, written by a select and highly respected group of leaders in this field, critically review evidence in a controversial area each author has contributed to and investigated during his career. In addition, the reader is also given insight into their clinical and personal experience. Difficult Decisions in Colorectal Surgery offers solutions to a broad array of difficult and often controversial problems that the surgeon who deals with colorectal disease often encounters. It is a current and timely reference source for practicing surgeons, surgeons in training, and educators that describes the recommended ideal approach, rather than customary care, in selected clinical situations. .
Introduction -- Evaluating evidence.-IBD/ Management of symptomatic anal fistulas in pts with Crohn$1 (Bs disease -- Management of a painful anal fissure and skin tags in pts with Crohn$1 (Bs disease -- Elective surgical management in patients with ulcerative colitis-how many stages? -- Which UC patients should not have IPAA? -- Management of pouch-vaginal fistulas -- IPAA for Crohn$1 (Bs colitis? -- Steroid management in patients undergoing surgery for IBD -- Management of dysplasia in patients with ulcerative colitis -- Postoperative prophylaxis in patients with Crohn$1 (Bs disease -- Colon cancer/ Followup in patients after curative resection for colon cancer -- Management of patients with acute large bowel obstruction from colon cancer,- Management of patients with colon cancer and synchronous liver metastases -- Management of the patient with an endoscopically unresectable cecal polyp -- Role of chemotherapy for resected Stage 2 colon cancer -- Rectal cancer/ Management of T1 rectal cancer -- Management of T2 rectal cancer -- Management of the pt with a complete clinical response after neoadjuvant chemoradiation -- Management of the patient with rectal cancer presenting with synchronous liver metastases -- Who needs a loop ileostomy after LAR for rectal cancer? -- Selection factors for reoperative surgery for local recurrent rectal cancer -- Anal dysplasia/ Management of patients with AIN 3 -- Management of the abnormal pap smear in HIV positive patients -- Benign colon disease/ Indications for surgery in patients with severe C dificile colitis -- Do we need to operate on patients after successful percutaneous drainage of a diverticular abscess? -- Acute surgery for Hinchey 3 diverticulitis-resect or washout? -- Surgery for acute complicated diverticulitis-Hartmann vs primary anastomosis -- Who needs elective surgery for recurrent diverticulitis? -- Deciding on IRA vs IPAA for FAP -- How do we select the operation for pts with rectal prolapse? -- Benign anal disease/ Optimal management of the transsphincteric anal fistula -- Management of the recurrent anovaginal fistula -- When to do surgery for the pt with an anal fissure -- Management of the recurrent fissure after LIS -- Third degree hemorrhoids-Who really needs surgery? -- Which patients with fecal incontinence require physiologic workup? -- Who are the right candidates for sacral nerve stimulation? -- When is an anal sphincter repair indicated? -- Quality improvement/ What role checklists? -- Where are we with bowel preps for patients undergoing colon resection?.-Are fast track pathways for laparoscopic surgery needed? -- What are the right ingredients for a successful fast track pathway for open surgery? -- Preventing readmission after colon and rectal surgery -- Technique/ What is the best approach to transanal surgery: TEM vs TAMIS vs traditional transanal excision.-/ Lap vs robotic vs open surgery for rectal cancer -- Reservoir construction after LAR-Who and what? -- Hand assisted vs multiport vs single port approaches to laparoscopic colectomy -- Management of an anastomotic leak after LAR -- Management of the unhealed perineal wound after proctectomy.s
Keywords: Medicine; Proctology; Rectum -- Surgery; Minimally invasive surgery; Medicine & Public Health; Colorectal Surgery; Minimally invasive surgery; Proctology